Characterization of patients with eye cancer in a hospital from Santiago de Cuba - Yailin Audivert Hung; Hazel Turiño Peña; Lesbia Eloina Rodríguez Báez; Irene Rojas Rondón; Mariblanca Rodríguez Purón (Centro Provincial de Información de Ciencias Médicas, 2022)
Introduction: The ocular neoplasm can affect the eye, annexes and orbit. The effective treatment depends on an early, presumptive and accurate diagnosis.   Objective: To characterize patients with eye cancer according to variables of interest.  Method: An observational, descriptive and retrospective study of 58 patients with eye malignancy confirmed by means of biopsy was carried out. They were assisted in the Ocular Plastic Surgery Service of the Ophthalmologic Center at Dr. Juan Bruno Zayas Alfonso Teaching General Hospital in Santiago de Cuba, from October, 2015 to the same period in 2020. The mean was used for the quantitative variables.  Results: In the series the mean age was of 62.49 years; there was a prevalence of the male sex (51.7 %) and the mixed race color of the skin (53.4 %). The most frequent localization of the tumoral lesions in the annexes was in the lids (53.4 %) and the conjunctive (41.4 %). The predominant histologic types were palpebral basal cell carcinoma (44.8 %) and squamous cell carcinoma of the conjunctive (41.4 %). The estadification of the tumor was established: T1 en 47 patients, T2 and T3 in 4, as well as T4 in 3.   Conclusions: The control of the eye cancer is very important, because it allows to trace strategies for the early diagnosis and the appropriate treatment of patients.